The Effect of SP2DK on Taxpayers' Argumentation to Tax Authorities: The Role of Taxpayer Understanding as a Mediating Variable - Ardi Firmansyah (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2026)
This study aims to analyze the effect of the Request for Explanation of Data and/or Information (Surat Permintaan Penjelasan atas Data dan/atau Keterangan, hereinafter referred to as SP2DK) on taxpayers' arguments presented to tax authorities, utilizing taxpayer understanding as a mediating variable. This research employs a qualitative descriptive method with a phenomenological approach, conducting interviews with taxpayers who received the SP2DK at the Kebon Jeruk Medium Tax Office (KPP Madya Kebon Jeruk). The findings indicate that the issuance of SP2DK significantly influences how taxpayers articulate their clarifications and arguments to the tax authorities. Taxpayers possessing a comprehensive understanding of taxation tend to provide arguments that are more rational, systematic, and strictly aligned with prevailing tax regulations. Furthermore, the SP2DK also serves as a catalyst, encouraging taxpayers to enhance their compliance in tax recording and reporting activities.